Remark
Why don't we just solve the expression, and then see which one of the answers fit.
Step One.
You are eventually going to divide by - a. On of the most confusing problems with inequality equations is what to do about a - division. The answer is (in this case) to add ax to both sides of the equation.
-ax + ax + 2b > 8 + ax
2b > 8 + ax
Step two
Solve for x. Subtract 8 from both sides.
2b - 8 > 8 - 8 + ax
2b - 8 > ax
Step 3
Divide by a
(2b - 8)/a > x
Step Four
Find the answer.
I'm getting none of the answers above.
==============
My answer is actually correct. The question now goes through the convoluted process of multiplying top and bottom of the answer by -1. Why I don't know. I suppose just so you can get an answer that is given.
If you do that, you get
(8 - 2b)/-a > x which is the first answer, I think.